MARINE BIODISCOVERY RESEARCH IN INDONESIA : CHALLENGES AND REWARDS - Ekowati Chasanah (JOURNAL OF COASTAL DEVELOPMENT, 2008)
Marine biodiscovery or bioprospecting activity is a search for marine products derived from marine biodiversity that can be developed for various industrial needs. Including in this activity is the process of identifying chemical compounds made by biological organisms which is often called natural product discovery. Indonesia, well known as a mega-diversity country, is one of the world hot sport of marine biodiversity. The richness of biodiversity is claimed as mirror of the richness of the chemical compounds, therefore, Indonesian waters might be rewarded with variety of chemical compounds thought to be an endless source of novel drugs and drug leads for pharmaceutical use. Up to 2007, at least 77 new compounds from 14 sponges and 19 new compounds from non-sponge organisms with pharmacological potential have been identified from Indonesian waters. To make this richness potentials becoming real in economic value, many factors should be considered. The bioactive is produced in small quantity, and the lengthy process from discovery step of a novel compound to the preclinical and clinical trials step is usually becoming a problem. Mari culture might be one among methods that can be developed in Indonesia to overcome the degradation hazard of marine resources. Conducive environment for investments, and improvement of technology on marine bioactive production through mariculture are factors to be improved to initiate and develop a sustainable biotechnology industries in Indonesia.